THE EFFECT OF ICE BREAKING ON THE CONCENTRATION OF EARLY CHILDHOOD LEARNING AT TK IT IBNU KALDUN CIREBON - Suminar, Ratna (Ridwan Institute, 2024)
This study aims to examine the influence of the ice breaking method on early childhood learning concentration at Ibnu Kaldun Cirebon IT Kindergarten. Along with the importance of concentration in the learning process, this study uses a quantitative approach with an experimental design. The study subjects consisted of 30 children aged 5-6 years who were divided into two groups: an experimental group that applied the ice breaking method and a control group that did not use it. Data was collected through observations and questionnaires filled out by educators. The results of the analysis showed that the experimental group experienced a significant increase in learning concentration compared to the control group, with a p value < 0.05. This indicates that the ice breaking method plays an important role in increasing children's attention and involvement in learning. This study recommends the application of ice breaking techniques as part of the teaching method in kindergarten to help children focus and improve their learning outcomes. These findings are expected to provide a positive sensation to educational practices at the early childhood level and provide guidance for educators in designing effective activities.